Online networks facilitating multidisciplinary healthcare: a novel strategy to curb COVID-19 - Prins, Henrieke; Knijp, Ineke; Hermanides, Gonneke; Blanker, Marco; Rokx, Casper (Integrated healthcare journal, 2022)
ObjectivesGlobal spread of COVID-19 at an unprecedented speed has heavily strained healthcare systems worldwide, and reliable alternatives to analogue healthcare are urgently needed.MethodsDuring the first COVID-19 wave in the Netherlands, we launched six regional online networks and analysed the activity and content in a qualitative mixed-methods manner.ResultsWe observed continued activity and collaboration on the platform between healthcare professionals at the different levels of care.ConclusionThe networks described here were launched successfully and have the potential to optimise the COVID-19 response.